Chemical equilibrium model of struvite precipitation from anaerobic digester effluents - Türker, Mustafa; Erdem, İpek Çelen (My University, 2011)
This project investigated the usefulness of a chemical equilibrium model to predict the extent of ammonia removal as struvite from the effluent of anaerobic digester treating molasses-based industrial wastewater. The chemical equilibrium model was established by taking into account the activity coefficient and thermodynamic properties of potential compounds that may coprecipitate. It was considered that struvite was the only potential compound that precipitated under the conditions studied. pKs value of struvite was estimated by fitting the model predictions to the experimental results and found to be between 11 and 12 when the temperature is kept at 37°C, at different Mg2+: NH+4: PO3-4 ratios and pH values which are lower than those reported in the literature. This indicates that struvite is more soluble in the wastewater studied here. The analysis of the precipitate and model predictions suggest that there is another compound present in the precipitate in addition to struvite, which is most likely Mg3 (PO4)2XH2O. © TÜBITAK. © 2011 Elsevier B.V., All rights reserved.
Keywords: Ammonia recovery; Chemical equilibrium model; Magnesium ammonium phosphate; Solubility product; Struvite